2012
DOI: 10.1002/adem.201200039
|View full text |Cite
|
Sign up to set email alerts
|

Graded Cellular Ceramics from Continuous Foam Extrusion

Abstract: Cylindrical SiOC foam filaments with a radial gradient in pore cell size were processed by continuous extrusion foaming of a methyl polysilsesquioxane. Upon leaving the extrusion nozzle foaming was initiated by pressure release which caused precipitation of supersaturated carbon dioxide from the polymer filament. Rapid cooling of the thin filaments generates a radial gradient of melt viscosity which gives rise for formation of closed cell morphology of isotropic pore cells in the core (diameter < 200 µm) and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Due to the foaming process (pore forming and release of gas), the formation of a gradient structure is often the case. These gradient structures, if properly controlled, are of interest for filtering applications or for thermal insulation Ceron-Nicolat et al 2012). …”
Section: Porous and Cellular Ceramicsmentioning
confidence: 99%
“…Due to the foaming process (pore forming and release of gas), the formation of a gradient structure is often the case. These gradient structures, if properly controlled, are of interest for filtering applications or for thermal insulation Ceron-Nicolat et al 2012). …”
Section: Porous and Cellular Ceramicsmentioning
confidence: 99%
“…The last PBA technique is the compressed gas injection. For now, it was performed only on the preceramic polymers (PPs) in which the gas solubility and the molecule size (the small molecule diffuses much faster) in the liquid system found to be effective for final pore characteristics . In a basic description, PPs were first saturated by CO 2 , followed by heating and/or rapid pressure drop initiating foaming and finally pyrolysis at high temperature resulting in the microcellular ceramic .…”
Section: Processing Strategiesmentioning
confidence: 99%
“…In a basic description, PPs were first saturated by CO 2 , followed by heating and/or rapid pressure drop initiating foaming and finally pyrolysis at high temperature resulting in the microcellular ceramic . The process was also adapted to a technical scale, that is extrusion coupled with simultaneous foaming by dissolved CO 2 , and obtain diverse‐shaped closed porosity polymer‐derived ceramics (PDCs) …”
Section: Processing Strategiesmentioning
confidence: 99%
“…For instance, Bruno et al . obtained superior mechanical properties of SiOC materials by extrusion . Zhang et al .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Bruno et al obtained superior mechanical properties of SiOC materials by extrusion. [9] Zhang et al reported the hierarchically ordered structures of a SiOC monolith by a freeze-casting method, which is favorable in applications such as gas separation and liquid filtration. [10] Tatsuhiro et al reported to prepare SiOC ceramics with excellent oxidation resistance using a direct foaming method.…”
Section: Introductionmentioning
confidence: 99%